PENYULUHAN PEMANFAATAN TEPUNG DAUN SINGKONG SEBAGAI BAHAN BAKU TAMBAHAN PELLET IKAN NILA (Oreochromis niloticus) “STUDI PADA KELOMPOK PEMBUDIDAYA IKAN SUMBER SARI MAKMUR KECAMATAN LOA KULU KABUPATEN KUTAI KARTANEGARA”. - Ana Mariana; Helminuddin; Komsanah Sukarti (Jurnal Pembangunan Perikanan dan Agribisnis, 2017)
The purpose of this research were determinan the readabality of adaption and the level of readability of try and adoption inovation of utilization of cassava flour as additional raw material of fish pellet of Pokdakan member in Sumber Sari Makmur. This research was conducted since March 2017 in Sumber Sari village Loa Kulu district Kutai Kartanegara Regency. The sampling method was used cencus to 11 respondents. The data used by primary data and secondary data, primary data was collected by survey method questionnaire and secondary data obtained from literature study. Data was analyzed by using qualitative and quantitative descriptive analysis. The results was obtained the readabality to adoption of utilization of cassava flour as additional Raw Material of Pellet Nile (Oreochromis niloticus) of Pokdakan member in Sumber Sari Makmur. It is known from 11 respondents that 9 (81,8%) of respondents as showed as high to adoption of that innovation.